Use of GnRH and PGF for synchronized ovulation and fixed-time inseminations - Kobayashi, Y.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2011)
Holstein cows and virgin heifers were treated with GnRH and PGF in a novel 2a ovulation synchronization protocol, which involves one fixed-time insemination. One injection of GnRH is given on a Monday morning, followed in 7 days with an injection of PGF . Approximately 32 hr later, ovula- 2a tion is induced with a second injection of GnRH, and one insemination is made 18 hr later. Control cattle were given one injection of PGF and inseminated at estrus. Preg- 2a nancy rates measured between 28 and 35 days after insemination by ultrasonography were slightly, but not significantly, higher in controls (52.9%) than in the ovulation synchronization treatment (44.3%). This treatment may be particularly well suited to cows in which estrus is rarely observed, as well as for synchronizing first or repeat services.
Keywords: PGF; GnRH; Ovulation synchronization; Pregnancy rates